PRINSIP IQTISHODUNA DALAM PRAKTIK KONSUMSI MUSLIM - Roisatun Kasanah (Hukum Islam, 2022)
This study aims to provide an overview of the principles of iqtishoduna in Muslim consumption practices and the interpretation of iqtishoduna from various cultural perspectives and social interactions in Muslim society. This research is included in library research, namely research in which data and information are obtained and collected from library sources (reading) in the form of books, research results, news, and other reading materials. The researcher found that consumption practices that are in accordance with the Iqtishoduna principles, namely fair, balanced, moderate, and simple, are very important to achieve benefits for individuals and the environment, including social. society, and nature. There are various opinions regarding consumption practices that are in accordance with the iqtishoduna principle and its relationship to materialism due to the different interpretations of each individual. Cultural differences and social interactions between community groups are also factors that influence Muslim understanding of consumption in accordance with the iqtishoduna principle.